2023
DOI: 10.1177/20406207231205637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BCR::ABL1 transcript type and droplet digital polymerase chain reaction on successful treatment-free remission in chronic myeloid leukemia patients who discontinued tyrosine kinase inhibitor

Hyunkyung Park,
Hyeong-Joon Kim,
Sang-Kyun Sohn
et al.

Abstract: Background: Droplet digital polymerase chain reaction (ddPCR) is an exact method of measurement. Objectives: We conducted this study to identify the prognostic factors for successful treatment-free remission in patients with chronic-phase chronic myeloid leukemia who discontinued tyrosine kinase inhibitors (TKIs). We also aimed to validate ddPCR for predicting molecular relapse. Design: This is a prospective, multicenter study. Methods: We enrolled patients treated with TKIs for at least 3 years with a confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…Similarly, patients treated more than 78 months with 2G-TKI were less likely to relapse after TKI discontinuation. These results were consistent with what Chen et al [3], Park et al [42] and Mahon et al [44] described before. They demonstrated that patients with a deeper and longer duration of MR prior to stopping TKI relapsed less.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similarly, patients treated more than 78 months with 2G-TKI were less likely to relapse after TKI discontinuation. These results were consistent with what Chen et al [3], Park et al [42] and Mahon et al [44] described before. They demonstrated that patients with a deeper and longer duration of MR prior to stopping TKI relapsed less.…”
Section: Discussionsupporting
confidence: 93%
“…However, our results are consistent with what Chen et al [18] observed in a large cohort of Asian patients treated with TKI, which supports that there are no differences among different regions and ethnic groups. The observed differences may be due to the fact that, according to our hypothesis, the transcript type by itself may not be sufficient to impact TFR, but it may have an effect with a longer duration of TKI treatment or a longer DMR [15,24,[38][39][40][41][42]. Pfirrmann et al [43] reported preliminary data from the EURO-Sky trial and proposed several models and prognostic factors related to MR 3.0 maintenance at 3 years after stopping TKI.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations